Applicability of Distortion Product Otoacoustic Emissions as a new health surveillance technique for hearing screening in industry - Soer, Maggi E. (Magdalena Elizabeth) (University of Pretoria, 2017)
Dissertation (M Communication Pathology)--University of Pretoria, 2016.